How the crisis is altering women’s roles in Syria - Haddad, Z (Refugee Studies Centre, University of Oxford, 2014)
The significance of women as both distributors and recipients has been pivotal to the implementation of humanitarian assistance but also points to the burgeoning of a new social dynamic that has come about as a result of the upheaval caused by the war.